SOSIALISASI REKOMENDASI WAKTU YANG BAIK UNTUK BERWISATA OLAHRAGA DI AREA TAMAN NASIONAL BOGANI NANI WARTABONE - Pauweni, Mirdayani; Aisah R. Pomatahu (Education and Talent Development Center of Indonesia, 2024)
The Community Service Program aims to increase awareness and knowledge of tourism managers regarding optimal time management for sports tourism activities, especially white water rafting. Sports tourism is usually used to fill vacation and free time and can be grouped into three types: active, passive, and nostalgic sports tourism. One of the main attractions in Bogani Nani Wartabone National Park is white water rafting, which is included in the active sports tourism category. This activity not only offers fun and physical challenges but also integrates the beauty of the surrounding nature. However, white water rafting has a level of risk that needs to be managed properly, especially related to weather factors and fluctuating river conditions. Therefore, choosing the right time is very important to minimize the risk of accidents and improve the tourist experience. The community service activities in Poduwoma Village were directed at white water rafting tourism object managers and carried out through four stages. These stages include socialization, focus group discussions, risk management simulations, and evaluation and review of activity results. During the implementation of the activities, the participation of tourism object managers was quite good, and they provided constructive feedback. The management is aware of the importance of re-planning the operational schedule of tourism, especially related to determining opening and closing times for rafting tourist attractions that take safety factors into account. Based on the activity results, it is recommended that there be a revision in the arrangement of service times, taking into account weather factors, river water discharge, and other relevant environmental conditions. Thus, it is hoped that rafting tourism can be managed more safely and sustainably while increasing comfort and safety for tourists.